Relationships between structural fat properties with sensory, physical and textural attributes of yeast-leavened laminated salty baked product - de la Horra, Ana Elizabeth (2017)
The aim of this study was to establish relationships between structural fat properties and sensory, physical and textural attributes of yeast-leavened laminated salty products. Refined bovine fat (MG1) and shortening (MG2), with a solid fat content (SFC) higher than 20% at temperature range of 15–35 °C were more viscous and less sensitive to temperature changes. The micrographs of dough|fat|dough sections corresponding to samples with MG1 and MG2 revealed a lower penetration of the fat sheet in the dough section due to the more entangled fat structures that did not allow a great flow throughout the dough layer. Consequently, the structure of laminated dough pieces made the systems highly resistant to deformation. The laminated dough pieces elaborated with these fats showed the highest increments in their height and maintained symmetry. Products with fat with least SFC and higher destructuration rate produced smoother laminated structures due to the presence of pores. While products with MG1 and MG2 showed tortuous images and complex structures, associated to layers and extended pores. MG1 and MG2 products were preferred (flavor and appearance) over those with MG3. The highest ranking samples in the acceptability analysis were symmetric, presented very flaky crusts and had a high level of lamination.